Sebuah Kajian Filosofis: Pendidikan Karakter Berbasis Nilai Dan Norma Pancasila Melalui Kegiatan Bina Pribadi Islami Di SMPIT Al-Izzah Serang - Mu'arif, Ibnu; Silalahi, Suandi (Universitas Sultan Ageng Tirtayasa, 2024)
This research aims to understand how Islamic Personal Development activities can contribute to the development of student character and identify the challenges faced in its implementation. It is hoped that good character education can shape students into individuals who are not only academically intelligent, but also have high morals and ethics in accordance with Pancasila values. The method used in this research is a qualitative approach with data collection techniques through interviews, observation and document analysis. Interviews were conducted with teachers, students and parents to obtain a comprehensive perspective regarding Islamic Personal Development activities and their impact on character education. Observations were carried out during the activity to see directly the learning process and interactions between students and supervisors. Documentation taken includes curriculum, teaching materials and relevant activity records. The collected data was then analyzed using descriptive analysis techniques to find themes that emerged from the research results. The results of the research show that Islamic Personal Development activities at SMPIT Al-Izzah Serang have succeeded in integrating Pancasila values into the student character learning process. Data shows that 90% of students feel they understand Pancasila values better after participating in this activity, and 90% of parents report positive changes in their children's behavior, such as being more disciplined and responsible.